Analisis Pengujian Pemutus Tenaga (PMT) 150 KV Bay Penghantar Tanjung Pura di Gardu Induk Pangkalan Brandan - Tanzil Al Malik; Zuraidah Tharo; Haris Gunawan (CV. Hawari, 2025)
Biannual preventive-maintenance results (2022 & 2024) for the 150 kV Tanjung Pura line bay circuit breaker at Pangkalan Brandan Substation confirm reliable performance. Offline tests with Kyoritsu 3125 (5 kV) and ISA CBA-2000/Megger evaluated insulation resistance, contact resistance, operating time and contact synchronization against SPLN 52-1:1984, KEPDIR 0520-2.K/DIR/2014 and OEM limits (≤120 % FAT, ≤120 ms for 150 kV). Insulation far exceeded 1 MΩ/kV: 315–428 GΩ (62 600–85 600 MΩ/kV) in 2022 and 181–190 GΩ (36 200–38 000 MΩ/kV) in 2024; the drop is within safe bounds and linked to instrument variance and insulator surface condition. Contact resistance stayed low at 36.0–38.7 µΩ (<40 µΩ), although resistive loss rose from 0.13–0.139 W to 0.435–0.468 W due to higher load current. Opening time was 37.3–38.9 ms and closing time 68.2–72.6 ms, both compliant. Contact synchronization measured 0.3–0.8 ms open and 3–3.4 ms close, well below the 10 ms limit. The breaker is operationally healthy. Recommendations: periodic instrument calibration, pre-test insulator cleaning, strict adherence to SOPs and safety standards, and improved crew coordination for future consistency and safety.